Peningkatan Pengetahuan Masyarakat Tentang Pemanfaatan Umbi Bit sebagai Suplemen Anemia pada Ibu Hamil dan Anak-anak di Kabupaten Kla - Ramayani, Septiana Laksmi (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2024)
Anemia is a condition characterized by a lower than normal number and size of red blood cells or hemoglobin concentration (11g/dL). This condition results in the impaired capacity of the blood to transport oxygen throughout the body. Anemia in pregnant women and children has a relatively high prevalence. The high incidence of anemia in Indonesia, especially in Klaten Regency, is also caused by a lack of nutritious food intake. Anemia prevention can be achieved by consuming foods rich in iron and vitamin C, taking iron supplements, and avoiding foods that hinder iron absorption, one of which is beetroot. The purpose of this community service activity is to provide knowledge about the use of beetroot as an anemia supplement for pregnant women and children in Klaten Regency. The implementation of this community service activity was carried out with a pretest, followed by an outreach activity on the use of beetroot as an anemia supplement, followed by a posttest and concluded with a practical session on making beetroot juice. Based on the community service activities conducted, there was an increase in public understanding of the use of beetroot as an anemia supplement for pregnant women and children. From the 10 questions given, there were 7 questions that showed an increase in understanding and 3 questions that showed no change, resulting in an average increase in understanding of 16.32%.